2009
DOI: 10.1111/j.1365-2265.2009.03532.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations of the BSCL2 and AGPAT2 genes in 10 families with Berardinelli–Seip congenital generalized lipodystrophy syndrome

Abstract: We have demonstrated four novel mutations of the BSCL2 and AGPAT2 genes responsible for Berardinelli-Seip syndrome and Brunzell syndrome (AGPAT2-related syndrome).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Mutations in three different genes (AGPAT2, BSCL2, and CAV1) have been identified to cause CGL type III [Agarwal et al, 2004;Ebihara et al, 2004;Miranda et al, 2009]. Mutations in PTRF-CAVIN were identified in CGL type IV [Cohn et al, 2007].…”
Section: Introductionmentioning
confidence: 98%
“…Mutations in three different genes (AGPAT2, BSCL2, and CAV1) have been identified to cause CGL type III [Agarwal et al, 2004;Ebihara et al, 2004;Miranda et al, 2009]. Mutations in PTRF-CAVIN were identified in CGL type IV [Cohn et al, 2007].…”
Section: Introductionmentioning
confidence: 98%
“…The primary transcript originally described ( 16 ) contained 11 exons with protein coding beginning (see below). Two additional missense mutations that cause lipodystrophy, not seipinopathy, are also located close to this glycosylation site; these are T78A and L91P ( 46 ). The L91 residue is particularly interesting in that it is well conserved among species that contain the NVS glycosylation site ( 45 ), indicating that this region of the protein may be critical for both protein stability and seipin function.…”
Section: Seipin Structurementioning
confidence: 99%
“…Magre et al ( 16 ) initially reported three main seipin mRNA isoforms in humans by Northern blotting at ‫ف‬ 1.8, ‫ف‬ 2.0, and ‫ف‬ 2.4 kb, considered in subsequent studies (and mutation, T78A (described below), in their other allele ( 46 ). It is surprising that this 7 amino acid deletion could generate lipodystrophy, since the C-terminal cytosolic tail is not required for fat body lipid accumulation in fl ies (see below) ( 47 ).…”
Section: Humansmentioning
confidence: 99%
“…Several dozen disease-causing variants have been described. 2 The following molecular defects have been reported: nonsense, missense, splice-site variants, deletions and insertions. 3 Most of them result in frameshift and/or truncated proteins, which are likely to lead to the complete loss of AGPAT2 function.…”
Section: Mutational Spectrummentioning
confidence: 99%